2006
DOI: 10.1186/bf03353375
|View full text |Cite
|
Sign up to set email alerts
|

Changes in groundwater levels or pressures associated with the 2004 earthquake off the west coast of northern Sumatra (M9.0)

Abstract: Associated with the 2004 earthquake off the west coast of northern Sumatra, changes in groundwater levels or pressures were observed at many observation stations in Japan which are more than 5000 km from the hypocenter. At 38 of the 45 observation stations, there were changes in groundwater levels or pressures. At the 10 observation stations in which the Ishii-type borehole strain instruments were established, changes in crustal strains were also observed. A major part of the changes in crustal strains and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 13 publications
2
25
0
3
Order By: Relevance
“…It has been considered that earthquake-induced oscillations in groundwater levels are mainly caused by transient oscillations due to crustal poroelastic deformation in an aquifer during the passage of seismic waves (Rexin et al 1962;Kitagawa et al 2006). The amplitude of the water level oscillations is enhanced at particular frequencies, depending upon the characteristics of the well-aquifer systems (Cooper et al 1965;Liu et al 1989;Kunugi et al 2000;Kitagawa et al 2011).…”
mentioning
confidence: 99%
“…It has been considered that earthquake-induced oscillations in groundwater levels are mainly caused by transient oscillations due to crustal poroelastic deformation in an aquifer during the passage of seismic waves (Rexin et al 1962;Kitagawa et al 2006). The amplitude of the water level oscillations is enhanced at particular frequencies, depending upon the characteristics of the well-aquifer systems (Cooper et al 1965;Liu et al 1989;Kunugi et al 2000;Kitagawa et al 2011).…”
mentioning
confidence: 99%
“…Torbidone spring (S5), whose ratio to the pre-event discharge would be infinite (as the spring was dry prior to the earthquake) is marked by an asterisk at water-level changes affecting, in a more permanent way, groundwater flow, is also well described in Yan et al (2014). Whereas the mechanism for explaining the first type of effects is substantially accepted as being transient oscillations due to crustal dynamic poro-elastic deformation in an aquifer during the passage of seismic waves (Rexin et al 1962;Kitagawa et al 2006;Yan et al 2014), the cause of permanent offsets, corresponding to sustained changes, is still debated.…”
Section: Discussionmentioning
confidence: 99%
“…Much research using data obtained from groundwater monitoring has been reported. Examples include groundwater drought evaluation [4][5][6][7], studies of the relationship between climate change and groundwater [8,9], groundwater quality variables [10,11], seawater intrusion [12], and earthquake observation through groundwater analysis [13][14][15][16][17]. When interpreting groundwater monitoring data, fundamental information regarding the hydrogeological characteristics, the groundwater flow system, its fluctuations, and the connectivity of aquifers must be obtained and understood.…”
Section: Introductionmentioning
confidence: 99%